Master’s degree in sexual and reproductive health: enhancing career development opportunities for midwives in Mali - Cheick S. Sidibé; Tanya Brückner; Prisca Zwanikken; Anke van der Kwaak; Lalla Fatouma Traoré; Ousmane Touré; Jacqueline E.W. Broerse; Marjolein Dieleman (BMC Medical Education, 2023)
Abstract Background Midwives’ contribution to improving outcomes for women and newborns depends on factors such as quality of pre-service training, access to continuing professional development, and the presence of an enabling work environment. The absence of opportunities for career development increases the likelihood that health professionals, including midwives, will consider leaving the profession due to a lack of incentives to sustain and increase motivation to remain in the field. It also limits the opportunities to better contribute to policy, training, and research. This study aimed to assess the influence of a Master in Sexual and Reproductive Health (SRH) at the INFSS on midwives’ career progression in Mali. Methods This mixed methods study was conducted using an online questionnaire, semi-structured interviews, and a document review. The study participants included graduates from two cohorts (N = 22) as well as employers, managers, and teachers of the graduates (N = 20). Data were analysed according to research questions, comparing, and contrasting answers between different groups of respondents. Results The study revealed that graduates enrolled in the programme primarily to improve their knowledge and skills in management and public health. The graduates’ expected roles are those of programme and health project manager and participation in planning and monitoring activities at national or sub-national level. The managers expected the programme to reflect the needs of the health system and equip midwives with skills in management and planning. The Master enhanced opportunities for graduates to advance their career in fields they are not usually working in such as management, research, and supervision. However, the recognition of the master’s degree and of the graduates’ profile is not yet fully effective. Conclusion The master’s degree in SRH is a capacity building programme. Graduates developed skills and acquired advanced knowledge in research and management, as well as a postgraduate degree. However, the master programme needs to be better aligned with health system needs to increase the recognition of graduates’ skills and have a more positive impact on graduates’ careers.